2016
DOI: 10.1111/crj.12440
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic pulmonary hemosiderosis in adults: review of cases reported in the latest 15 years

Abstract: Background: Idiopathic pulmonary hemosiderosis (IPH) is a rare disorder of unknown etiology which can cause diffuse alveolar hemorrhage. IPH is found primarily in children. In adults, however, it is extremely rare. A systematic review was applied to identify the details of IPH in adults. Methods: Articles of English or Chinese language published between 2000 and 2015 were included. Data were extracted on the clinical features, examinations, treatments and clinical outcome. Results: A total of 37 cases of adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 24 publications
1
37
0
2
Order By: Relevance
“…However, the number of feline cases was relatively small, limiting the conclusions that could be drawn regarding the association of hemosiderosis with particular conditions, types of pulmonary disease, and the absence of pulmonary disease. A cause for pulmonary hemosiderosis is not always identified in humans, and various environmental factors such as inhalation of mold spores have been implicated . Although chronic exposure to toxic mold has been associated with severe pulmonary hemorrhage under anesthesia in two cats, a potential relationship between environmental agents and frequency of hemosiderosis in cats and dogs remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the number of feline cases was relatively small, limiting the conclusions that could be drawn regarding the association of hemosiderosis with particular conditions, types of pulmonary disease, and the absence of pulmonary disease. A cause for pulmonary hemosiderosis is not always identified in humans, and various environmental factors such as inhalation of mold spores have been implicated . Although chronic exposure to toxic mold has been associated with severe pulmonary hemorrhage under anesthesia in two cats, a potential relationship between environmental agents and frequency of hemosiderosis in cats and dogs remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…The conditions prior to BAL procedures that were specifically recorded were the presence of gastrointestinal (GI) diseases, autoimmune diseases, neoplasia, and osteoarthrosis. These diseases have been reported to be associated with pulmonary hemosiderosis in human medicine . A previous diagnosis of GI disease was based on vomiting and/or diarrhea for a 1‐week duration or longer.…”
Section: Methodsmentioning
confidence: 99%
“…The pulmonary symptomatology in LHS starts usually in childhood, and only 25% of all patients have an adult onset [14,35]. Xi-Yuan et al reviewed the literature for IPH and identified 37 patients (12 women, 24 men), out of whom 5 had CD [64]. In children with IPH, about 30% might have associated CD [65].…”
Section: Discussionmentioning
confidence: 99%
“…Idiopathic Pulmonary Hemosiderosis is treated with systemic corticosteroids with or without other immunosuppressant. 15 DAH is often misdiagnosed as radiology mimics other alveolar filling processes such as infection and pulmonary edema. The low index of suspicion is another cause of delayed diagnosis.…”
Section: A 4bmentioning
confidence: 99%